A powerful phenotype for gene‐finding studies derived from trajectory analyses of symptoms of anxiety and depression between age seven and 18. Issue 7 (3rd September 2015) - Lubke, Gitta H.; Miller, Patrick J.; Verhulst, Brad; Bartels, Meike; van Beijsterveldt, Toos; Willemsen, Gonneke; Boomsma, Dorret I.; Middeldorp, Christel M.
Abstract : To investigate the utility of longitudinal data in genetic analyses of symptoms of anxiety and depression, we assessed individual differences between age 7 and 18 using growth mixture models, and investigated the genetic and non‐genetic factors contributing to the trajectories. Mothers of 7, 706 girl and 7, 418 boy twins from the Netherlands Twin Register rated the anxious depression scale (SxAnxDep) of the Child Behavior Check List (CBCL) at age 7, 10, and 12 years. Two thousand seven hundred and six girl and 1, 856 boy twins completed the Youth Self Report (YSR) at age 14, 16, and 18. While individual trajectories varied considerably, these differences were largely idiosyncratic and could not be grouped into separate latent classes with class‐specific average growth curves. The intercept, which reflects the individuals' baseline level of SxAnxDep across time, explained 55–58% of the total phenotypic variance. The slope factor, which captures a common average trend over time, did not explain variance in the phenotype. This finding also underlines the high level of idiosyncrasy of trajectories that lack a common longitudinal structure. The analyses of twin data showed that the random intercept factor of SxAnxDep during childhood and during adolescence is considerably more heritable than the observations at any single age, namely between 60% and 84%. One explanation is that different factors contribute to the level of symptoms of anxiety and depression at any given time point, including temporary events and emotions. When considering baseline stability, these temporary influences average out, with the result of a more reliable and more heritable phenotype. © 2015 Wiley Periodicals, Inc.